THE ACTUAL LEVEL OF PENSION PROVISION IN RUSSIA - V. Skotarenko, Oksana; V. Bespalova, Svetlana; B. Seneckaya, Larisa (Revista Gênero e Interdisciplinaridade, 2020)
The problem of the pension system modernization focused on improving Russian citizens’ standard of living remains relevant in contemporary Russia. The study aims at developing proposals to improve the living standards for citizens of retirement age in Russia in the context of pension system reforms. Systematic methodological approach and methods of statistical and economic analysis, including methods of horizontal and vertical analysis, enabled assessments of the dynamics and structure of revenue and expenditure of the Pension Fund, the number of working pensioners in the Russian Federation. The calculation of pension for individuals is carried out by ratio analysis. The comparative analysis enabled the assessment of differences in living standards of pensioners in the Far North and other regions of Russia. The study has determined the reasons for continued employment of pensioners in the Russian Federation; the pension scheme for individuals; perspective directions to improve the pension system. The core of the study is to substantiate the need to reform the pension system focused on improving the living standards for citizens of retirement age in the Russian Federation.